(untitled) (London Journal of Medical and Health Research, 2023)
Rabies antibody titres in dogs (aged ≥ 3 months) which had been vaccinated with the Ptovac® Anti- rabies vaccine brand and administered B-vitamins, post vaccination, in Nigeria, were assessed by passive haemagglutination (PHA) test. The groups were named: Treated with B-vitamins (Vetzyme®) for one day post vaccination; Treated with B-vitamins for two days post vaccination; Treated with B-vitamins for three days post vaccination and Control. Two weeks post vaccination, serum from each dog was tested for rabies antibodies by PHA. Antibody titres in the groups differed, significantly (P≥ 0.05), from 24.74±0.08 in the control to 64.08±0.03 in Treated with B-vitamins for one day post vaccination, 89.29±0.17 in Treated with B-vitamins for two days post vaccination and 140.73±0.14 in Treated with B-vitamins for three days post vaccination. Adopting post vaccination B-Vitamins` treatment and routine assessment of immune response of dogs to anti-rabies vaccinations could improve success of rabies control-efforts in the country.